2020
DOI: 10.1371/journal.pone.0229396
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nutritional evaluation of patients with hepatic alveolar echinococcosis

Abstract: This study is aimed at determining the preoperative nutritional status of patients with hepatic alveolar echinococcosis (HAE), and subsequently establish a concise and reasonable nutritional evaluation indicator. The established evaluation method could be used for clinical preoperative risk assessment and prediction of post-operation recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Based on the prognostic prediction model, the nutrition and liver function of patients are not as important as the pathological indices of the tumor. Nevertheless, they can be improved by nutritional support therapy, liver protection therapy, and immune support therapy before operation 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the prognostic prediction model, the nutrition and liver function of patients are not as important as the pathological indices of the tumor. Nevertheless, they can be improved by nutritional support therapy, liver protection therapy, and immune support therapy before operation 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main mechanism of pain sensitivity caused by hypertension is impaired cardiovascular regulation. 23 Considering that BMI can be used to assess body’s nutritional status, 24 , 25 we speculate that BMI effects on pain may be related to impaired vascular regulation. But this needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the nutritional and immunological statuses affect postoperative outcomes [ 11 ]. Alveolar echinococcal disease is also a disease with severe inflammation, and it is known that the inflammatory process plays a vital role in all its stages [ 12 ]. Many parameters related to preoperative prognostic indicators have been studied, but the high cost, lack of standardization, and unsuitability for widespread use of these parameters have limited their clinical use.…”
Section: Discussionmentioning
confidence: 99%